2020
DOI: 10.3390/nano10102040
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Features of Gold Nanoparticles Interaction with HepG2 and HEK293 Cells in Monolayer and Spheroids

Abstract: Use of multicellular spheroids in studies of nanoparticles (NPs) has increased in the last decade, however details of NPs interaction with spheroids are poorly known. We synthesized AuNPs (12.0 ± 0.1 nm in diameter, transmission electron microscopy (TEM data) and covered them with bovine serum albumin (BSA) and polyethyleneimine (PEI). Values of hydrodynamic diameter were 17.4 ± 0.4; 35.9 ± 0.5 and ±125.9 ± 2.8 nm for AuNPs, AuBSA-NPs and AuPEI-NPs, and Z-potential (net charge) values were −33.6 ± 2.0; −35.7 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…An exploration of gold nanorods, nanospheres, and oligonucleotide-functionalized nanospheres was undertaken by Rane et al who showed the difference in uptake profiles present in a 3D model compared to the 2D monolayer [ 43 ]. Further studies on how functionalization and size of the GNPs have been explored recently, all agreeing that smaller GNPs will more effectively penetrate deeper into the cells [ 44 , 45 ]. More complex in vivo systems can also be reproduced in a spheroid model, such as a blood-brain barrier made up multiple cell types in a multicellular spheroid.…”
Section: Introductionmentioning
confidence: 99%
“…An exploration of gold nanorods, nanospheres, and oligonucleotide-functionalized nanospheres was undertaken by Rane et al who showed the difference in uptake profiles present in a 3D model compared to the 2D monolayer [ 43 ]. Further studies on how functionalization and size of the GNPs have been explored recently, all agreeing that smaller GNPs will more effectively penetrate deeper into the cells [ 44 , 45 ]. More complex in vivo systems can also be reproduced in a spheroid model, such as a blood-brain barrier made up multiple cell types in a multicellular spheroid.…”
Section: Introductionmentioning
confidence: 99%
“…The materials in these studies are however encountered as bulk materials, assessed for occupational or environmental safety, and thus they are not NBMs developed for medical uses or medical technology, like the materials presented in this study. To date, very few publications have used 3D hepatocellular carcinoma models for assessing toxicity of NBMs, with most studies utilising spheroids to assess depth and penetrations of NBMs in 3D [73][74][75][76][77]. To the best of our knowledge, this study is the first time 3D liver spheroids have been used in the in vitro toxicity screening of these specific NBMs, making the work presented an advancement in the nanomedicine field.…”
Section: Discussionmentioning
confidence: 99%
“…These materials however are ones which may been encountered occupationally and are not technically NBMs which can be applied to medical technology, like the materials presented in this study. To date, very few publications have used 3D liver models for assessing toxicity of NBMs, with most studies utilising spheroids to assess depth and penetrations of NBMs in 3D[49][50][51][52][53], and to the best of our knowledge this study in vitro toxicity screening, making the work presented in this work a signi cant advance in the eld.…”
mentioning
confidence: 99%